Advanced mechanisms for the promotion of renewable energy: models for the future evolution of the German Renewable Energy Act - Ole Langniß; Jochen Diekmann; Ulrike Lehr (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
The German Renewable Energy Act (EEG) has been very successful in promoting the deployment of wind power plants and other renewable energy power generating technologies in Germany. The increasing share of EEG-power in the generation portfolio, increasing amounts of fluctuating power generation, and the growing European integration of power markets governed by competition calls for a re-design of the EEG. This article identifies increasingly important problems and describes three different options to amend the EEG without jeopardising the fast deployment of renewable energy technologies. In the Retailer Model, it becomes the responsibility of the end-use retailers to adapt the EEG power to the actual demand of their respective customers. The Market Mediator Model is the primary choice when new market players are regarded as crucial for the better integration of renew-able energy and enhanced competition. The Optional Bonus Model relies more on functioning markets.
Keywords: 330; Regulation; Renewable Energy; Promotion; Policy Design; Feed-In Tariff; Minimum Price Standards; Förderung regenerativer Energien; Reform; Policy-Mix; Staatliche Preispolitik; Deutschland